Comparative Study of Leading Cruise Lines’ Sustainability Practices and Environmental Stewardship in Contribution to SDGs’ Sea and Water Conservation Goal - Pakbeen, Hesam (European Journal of Sustainable Development, 2018)
Cruise vacation is one of the fastest growing segments of tourism industry. Cruise Lines International Association (CLIA) reports that in 2017 nearly 26 million ocean cruise passengers were carried globally, which is expected to reach 27.2 million passengers in 2018. In terms of environmental impacts, however, the growth of the industry has raised increased concerns. Accordingly, environmental regulations, policies and commitments urge the cruise lines to conduct sustainability practices and report on their environmental stewardship. In contribution to UN’s Sustainable Development Goals (SDGs), the cruise industry can be a significant enabler for positive impact, distinctly on environmental goals. The present paper reviews environmental stewardship and practices of the leading cruise lines in contribution to goal No.14 of SDGs, referring to “life below water”. The objective of this study is to investigate how sustainability strategies and practices of leading cruise companies responded to water and sea conservation goal. The study includes an outline of cruise industry, growth and impacts following by exploratory review of sustainability and corporate responsibility reporting of major cruise lines. The findings of the research are based on evaluation and comparison of (1) practices and actions, (2) strategies and goal settings, and (3) cooperation and partnership of cruise lines, in regard with water and sea conservation goal of SDGs. Keywords: Cruise industry, Environmental stewardship, SDGs (Sustainable Development Goals), Sea and Water conservation